Calculation:

Consider the expression, \(\displaystyle\sqrt{{{11}{t}}}\).

Use the property, \(\displaystyle\sqrt{{{n}}}{\left\lbrace{a}^{{{m}}}\right\rbrace}={a}^{{^{\left\lbrace{m}\angle{n}\right\rbrace}}}.\)

Here, \(\displaystyle{m}={1}\ \text{and}\ {n}={2}\)

Then, the expression \(\displaystyle\sqrt{{{11}{t}}}\) can be written as

\(\displaystyle\sqrt{{{11}{t}}}=\sqrt{{{\left({11}{t}\right)}}}\)

\(\displaystyle={\left({11}{t}\right)}^{{^{\left\lbrace{1}\angle{2}\right\rbrace}}}\)

Thus, the required expression is \(\displaystyle{\left({11}{t}\right)}^{{^{\left\lbrace{1}\angle{2}\right\rbrace}}}.\)

Consider the expression, \(\displaystyle\sqrt{{{11}{t}}}\).

Use the property, \(\displaystyle\sqrt{{{n}}}{\left\lbrace{a}^{{{m}}}\right\rbrace}={a}^{{^{\left\lbrace{m}\angle{n}\right\rbrace}}}.\)

Here, \(\displaystyle{m}={1}\ \text{and}\ {n}={2}\)

Then, the expression \(\displaystyle\sqrt{{{11}{t}}}\) can be written as

\(\displaystyle\sqrt{{{11}{t}}}=\sqrt{{{\left({11}{t}\right)}}}\)

\(\displaystyle={\left({11}{t}\right)}^{{^{\left\lbrace{1}\angle{2}\right\rbrace}}}\)

Thus, the required expression is \(\displaystyle{\left({11}{t}\right)}^{{^{\left\lbrace{1}\angle{2}\right\rbrace}}}.\)